Studying the impact of emotion-AI in cross-cultural communication on the effectiveness of global media - Fangni, Li (Frontiers in Computer Science, 2025)
IntroductionEmotion-AI, which integrates artificial intelligence in recognizing and processing emotions, holds significant potential in enhancing cross-cultural communication, particularly in global media contexts. This study investigates the impact of emotion-AI on global media communication, focusing on its role in bridging cultural gaps, fostering emotional connections, and improving cross-cultural understanding.MethodA descriptive cross-sectional survey using structured questionnaires collected data from 1,108 global media consumers. Fuzzy-set qualitative comparative analysis (fsQCA) assessed participants' media-related emotion-AI experiences, perceptions, and reactions.ResultEmotion-AI's capacity to deepen emotional relationships (62.1%) and respect for cultural diversity (62.7%) is well-known and appreciated. However, there are still many people who are worried about emotions being oversimplified (34.7%), which shows that technology cannot handle nuanced cultural manifestations of emotion just yet. Also, many look forward to seeing emotion-AI improve in the future, especially when it comes to fixing its present problems. With a solution coverage of 93% and consistency of 81%, the analysis further shows that positive experiences and perceptions are needed to create pleasant reactions. This highlights the crucial relevance of cultural adaptability and emotional accuracy in global media environments.DiscussionThis study sheds light on emotion-AI's involvement in cross-cultural communication and global media efficacy, affecting system development, and content integration. Emotion-AI could improve global communication by recognizing cultural differences and encouraging cultural tolerance.